Heat, health, and humidity in Australia's monsoon tropics: a critical review of the problematization of 'heat' in a changing climate. (24th May 2017) - Oppermann, Elspeth; Brearley, Matt; Law, Lisa; Smith, James A.; Clough, Alan; Zander, Kerstin
Abstract : Exposure to heat has killed more people in Australia than all other natural hazards combined. As the climate warms, temperatures are projected to rise substantially, increasing the impact of heat stress and heat illness nation‐wide. The relation between heat and health is profoundly complex, however, and is understood differently across multiple sectors. This paper thus provides a critical review of how heat is currently measured and managed in Australia, highlighting how humidity, exposure, and exertion are key elements that are not consistently incorporated into 'problematizations' of heat. The presence or absence of these elements produces different spatial and temporal geographies of danger, as well as different governance practices. In particular, the invisibility of humidity as having a significant impact on heat and health shapes whether Australia's tropical monsoon zone is visible as a region at risk or not, and whether prolonged periods of seasonal heat are treated as dangerous. Similarly, different populations and practices become visible depending on whether the human body (its exposure, exertion, cooling, and hydration) is included in accounts of what constitutes 'heat.' As a result, the outdoor, manual workforce is visible as a population at risk in some accounts but not others. A brief review of key policy areas including housing, public health and work health and safety is presented to demonstrate how specific problematizations of heat are critical to the identification of, and response to, current and future climatic conditions. This has implications for how populations, places, and practices are constituted in the region. WIREs Clim Change 2017, 8:e468. doi: 10.1002/wcc.468 This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Behavior Change and Responses Vulnerability and Adaptation to Climate Change > Values‐Based Approach to Vulnerability and Adaptation Policy and Governance > Governing Climate Change in Communities, Cities, and Regions Abstract : Understanding heat and health in Australia's monsoon tropics.